2007
DOI: 10.1128/jvi.00432-07
|View full text |Cite
|
Sign up to set email alerts
|

Type- and Subcomplex-Specific Neutralizing Antibodies against Domain III of Dengue Virus Type 2 Envelope Protein Recognize Adjacent Epitopes

Abstract: Neutralization of flaviviruses in vivo correlates with the development of an antibody response against the viral envelope (E) protein. Previous studies demonstrated that monoclonal antibodies (MAbs) against an epitope on the lateral ridge of domain III (DIII) of the West Nile virus (WNV) E protein strongly protect against infection in animals.Based on X-ray crystallography and sequence analysis, an analogous type-specific neutralizing epitope for individual serotypes of the related flavivirus dengue virus (DEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
336
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(350 citation statements)
references
References 82 publications
11
336
2
1
Order By: Relevance
“…3B), and no binding to prM was observed, with the exception of the pooled human serum that was used as a positive control. All mAb clones were also tested for binding to EDIII, the E protein domain that contains the most effective neutralizing epitopes (34,35). However, none of the Abs tested bound to EDIII, at least not to the soluble monomeric form used in these assays (Table II).…”
Section: Pb Abs Bind To the Virus Surface E Proteinmentioning
confidence: 99%
“…3B), and no binding to prM was observed, with the exception of the pooled human serum that was used as a positive control. All mAb clones were also tested for binding to EDIII, the E protein domain that contains the most effective neutralizing epitopes (34,35). However, none of the Abs tested bound to EDIII, at least not to the soluble monomeric form used in these assays (Table II).…”
Section: Pb Abs Bind To the Virus Surface E Proteinmentioning
confidence: 99%
“…Extensive antibody mapping studies using mouse mAbs have identified at least 12 different epitopes on the surface of the E protein, with those located on ED3 eliciting some of the most potent neutralizing antibodies Roehrig et al, 1998). Furthermore, two major overlapping antigenic sites have been identified on ED3 and include the DENV type-specific and DEN complex-reactive antigenic sites Gromowski et al, 2008;Roehrig et al, 1998;Sukupolvi-Petty et al, 2007). Epitope mapping studies have demonstrated that these sites are composed of a small number of critically important residues (i.e.…”
mentioning
confidence: 99%
“…Epitope mapping studies have demonstrated that these sites are composed of a small number of critically important residues (i.e. critical residues) that significantly reduce antibody binding to recombinant ED3 when mutated Gromowski et al, 2008;Hiramatsu et al, 1996;Sukupolvi-Petty et al, 2007). Critical residues composing the DENV-2 type-specific antigenic site are lysine at position 305 and proline at position 384 (Figs 1a and S1, available in the online Supplementary Material), whereas, the DEN complexreactive antigenic site is composed of one critical residue, lysine at 310 (Fig.…”
mentioning
confidence: 99%
“…Dengue is an infection caused by the dengue virus (DENV) of the Flaviviridae family (Sukupolvi-Petty et al 2007) and is transmitted by infected female mosquitoes (Bhatt et al 2013;Kyle & Harris 2006). Dengue virus has four serotypes (DENV-1 to -4) that genetically share ~65% similarities (Mustafa et al 2015).…”
Section: Introductionmentioning
confidence: 99%